2021
DOI: 10.1155/2021/6656298
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated lncRNA NKILA Enhances the Secretory Function of Airway Epithelial Cells Stimulated by Mycoplasma pneumoniae via NF-κB

Abstract: The secretory function of airway epithelial cells is important in the pathogenesis of Mycoplasma pneumoniae pneumonia (MPP). To investigate the regulatory function of NKILA (nuclear factor-κB (NF-κB) interacting long noncoding RNA (lncRNA)) in MPP, we first detected NKILA as well as the concentration of interleukin 8 (IL-8) and tumor necrosis factor-α (TNF-α) in bronchoalveolar lavage fluid of children with MPP. Then, NKILA was knocked down in epithelial cells to investigate its effect on their secretory funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Referring to the relevant research, we found that some special genes on virulence plasmids are considered to be the best markers for identifying hvKP at present [ 10 ]. Among them, lncRNA NKILA (NKILA) is a gene that has been proved to be abnormally expressed in patients with sepsis and HIV-1 infection [ 11 , 12 ]; as for pneumonia, NKILA has also been found to exert a certain regulatory effect on the epithelial cytotoxicity of mycoplasma pneumoniae [ 13 ]. Therefore, we speculate that NKILA may also have important reference significance in hvKP.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the relevant research, we found that some special genes on virulence plasmids are considered to be the best markers for identifying hvKP at present [ 10 ]. Among them, lncRNA NKILA (NKILA) is a gene that has been proved to be abnormally expressed in patients with sepsis and HIV-1 infection [ 11 , 12 ]; as for pneumonia, NKILA has also been found to exert a certain regulatory effect on the epithelial cytotoxicity of mycoplasma pneumoniae [ 13 ]. Therefore, we speculate that NKILA may also have important reference significance in hvKP.…”
Section: Introductionmentioning
confidence: 99%
“…Since many of the highly dysregulated lncRNA genes by Mg and Mp are new and their functions in the cellular processes are yet to be determined, we wanted to know whether Mg and Mp regulate any of the lncRNAs that were previously implicated in infection and immune response [ 10 , [22] , [23] , [24] , 51 , 52 ]. To accomplish this, a list of about thirty lncRNA genes ( Table S10 ) with known functions in infection and immune response was made, and their presence or absence was tracked within the lncRNAs up- and down-regulated by Mg or Mp or by both.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it was previously reported that MALAT1 expression is higher [ 51 ] and NKILA, another lncRNA, expression is lower in the bronchoalveolar lavage fluid of children with Mp-related pneumonia than in the control subjects without pneumonia [ 52 ]. Human alveolar epithelial cell lines A549 infected with Mp also showed a similar trend of higher MALAT1 expression and lower NKILA expression accompanied by increased IL-8 and TNF-α [ 51 , 52 ]. It should be noted here that the expression of NKILA is downregulated in Mp-infected HeLa cells, although it was neither upregulated nor downregulated in Mg-infected HeLa cells ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations